1998
DOI: 10.1046/j.1365-2230.1998.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

Desquamative gingivitis and balanitis - linear IgA disease or cicatricial pemphigoid?

Abstract: A 38-year-old man presented with gingival inflammation together with erosions of the penis. Direct immunofluorescence demonstrated linear deposits of IgA at the basement membrane zone; indirect immunofluorescence and immunoblotting were negative. Linear IgA disease (LAD) was therefore suspected and treatment with dapsone initiated but this was changed to sulfamethoxy-pyridazine and systemic corticosteroids because of methaemoglobinaemia. During 1-year follow-up the lesions continued to wax and wane although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Since the publication of the consensus in 2002 (Chan et al , ), 15 cases have been published and the large majority of them (73%) by oral medicine specialists (Table ). Four of the cases included in Table were diagnosed and published as cases of MMP (Leonard et al , ; Hietanen et al , ; Kirtschig et al , ). Twenty‐five of 29 (86%) had oral lesions and 18 (62%) had exclusive oral, in most of the cases, gingival lesions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the publication of the consensus in 2002 (Chan et al , ), 15 cases have been published and the large majority of them (73%) by oral medicine specialists (Table ). Four of the cases included in Table were diagnosed and published as cases of MMP (Leonard et al , ; Hietanen et al , ; Kirtschig et al , ). Twenty‐five of 29 (86%) had oral lesions and 18 (62%) had exclusive oral, in most of the cases, gingival lesions.…”
Section: Resultsmentioning
confidence: 99%
“…DDS therapy may cause a variety of adverse effects, which may be categorized as pharmacologic, dose dependent, and allergic, or idiosyncratic reactions (Gürcan and Ahmed, ). Some degree of anemia is common using DDS but also severe adverse effects such as meta‐hemoglobinemia (Kirtschig et al , ), agranulocytosis (Raizman et al , ), DDS hypersensitivity syndrome (Risse et al , ), and peripheral neuropathy (Foster, ) have been reported in patients with MMP. AE are supposed to be dose related and mostly not serious at daily dose below 100 mg, but the evidences are controversial (Table ).…”
Section: What Is the Best Therapeutic Option For Mmp?mentioning
confidence: 99%
“…An exclusive mucosal involvement has been reported very rarely in LAD (Table 1) (Kumar et al , 1980; Porter et al , 1990, 1992; Kirtschig et al , 1998; Cohen et al , 1999; Egan et al , 1999; Lazzaro and Lazzaro, 1999; Letko et al , 2000; Eguia del Valle et al , 2003; Talhari et al , 2006; Angiero et al , 2007; Lewis et al , 2007). All 14 patients were adult (mean age 61 years, range 29–79); males / females ratio was 7/6.…”
Section: Reported Cases Of Linear Iga Disease With Exclusive Mucosalmentioning
confidence: 99%
“…The methodology for the detection of antibody activity against laminin 332 and P200 has been previously described 9,15 …”
Section: Methodsmentioning
confidence: 99%
“…Patients with CP may have concomitant skin lesions resembling classic bullous pemphigoid (BP). Also there are other autoimmune vesiculobullous disorders that mimic CP by virtue of associated scarring – namely epidermolysis bullosa acquisita (EBA) and linear IgA disease 8,9 …”
Section: Introductionmentioning
confidence: 99%